Desempenho no exercício de sprint intervalado de vegetarianos estrito e onívoros praticantes de atividade física - Pfeiffer, Astrid (2021)
There is a popular belief that the lack of certain nutrients in a vegan diet, such as a lower consumption of creatine and carnosine, can impair performance in repeated sprint exercises. However, no study has tested this hypothesis. Thus, the aim of the present study was to compare performance during a sprint interval exercise between vegans and physically active omnivores. Nine paired healthy vegans (4 men and 5 women) and nine healthy omnivores (4 men and 5 women) were paired and presented similar body weight, height and levels of daily physical activity. During two fully days prior to the test, participants described their meals. In the analysis of food records, vegans had a higher percentage of total energy intake of carbohydrates, fibers and magnesium than omnivores. On the other hand, vegans consumed less fat, cholesterol, monounsaturated fatty acid, saturated fatty acids, trans fatty acids, calcium, phosphorus, selenium, sodium, zinc, retinol, cobalamin, riboflavin, niacin and calciferol, when compared to omnivores (p<0.05). There was no difference between vegans and omnivores in relation to carbohydrates (g, g. kg-1 and kcal) and proteins (g, g. kg-1, kcal and % of total energy intake) (p>0.05). In relation to the sprint test, participants performed four sprints of 30 seconds pedaling as fast as possible against a resistance of 0.075 kg. kg-1 of body weight (5 minutes of passive rest between the sprints) in a cycle ergometer. Peak power, mean power, fatigue index and the time to reach maximum power in each sprint were recorded. There was a higher peak power in series 1 and 2 compared to series 3 and 4 (p<0.05), and a greater mean power in series 1 compared to series 2, 3 and 4 (p<0.05). However, for all series, there was no significant difference between vegans and omnivores in peak and mean power (p>0.05). The fatigue index and the time to reach maximum power not affected by the diet or by the sprints (p>0.05). The results of the present study suggest there is no significant difference between physically active vegans and omnivores in relation to their performance during repeated sprint exercise.